Analysis of The Quality of Hajj Embarkation Services in Gorontalo Province in 2022 - Latif, Abdul; Habu, Azhar D; Sahabi, Ansar; Muhdar HM; Mardiana, Andi; Salwa S, Andi (Al-Ulum, 2024)
This study assesses customer satisfaction with the Embarkation Services for Hajj Pilgrims in Gorontalo. A mixed-methods approach was used, involving a survey of 50 pilgrims via a social media-distributed questionnaire. The survey, based on a Likert scale, covered eight main aspects and 24 sub-aspects. The research results showed a satisfaction index of 8,11, indicating a good level of satisfaction. Organisers should heed pilgrims' feedback to improve service quality and provide staff training. Regular service quality evaluations and enhancements to pilgrims' comfort are recommended to significantly advance the Hajj embarkation services in Gorontalo.